2010
DOI: 10.1097/ijg.0b013e3181ca7f7f
|View full text |Cite
|
Sign up to set email alerts
|

The Ahmed Glaucoma Valve in Patients With and Without Neovascular Glaucoma

Abstract: Neovascular glaucoma patients have greater risk of surgical failure after Ahmed Glaucoma Valve surgery compared with controls. Despite improved IOP with drainage implants, visual outcomes may be poor, probably owing to progression of underlying disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 19 publications
3
37
0
2
Order By: Relevance
“…Indeed, a valve mechanism has been introduced in an attempt to prevent complications sometimes encountered with non-valved GDIs, such as hypotony, shallow anterior chamber, choroidal effusion and choroidal detachment [14]. Several studies have shown that AGV is safe and effective in reducing IOP in patients with primary [15][16][17], secondary [18][19][20][21][22][23][24] and refractory glaucoma [25][26][27]. However, the hypotensive efficacy of AGV in comparison with other anti-glaucoma interventions has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a valve mechanism has been introduced in an attempt to prevent complications sometimes encountered with non-valved GDIs, such as hypotony, shallow anterior chamber, choroidal effusion and choroidal detachment [14]. Several studies have shown that AGV is safe and effective in reducing IOP in patients with primary [15][16][17], secondary [18][19][20][21][22][23][24] and refractory glaucoma [25][26][27]. However, the hypotensive efficacy of AGV in comparison with other anti-glaucoma interventions has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы, эффективность дренажной хирургии при рефрактерной глаукоме значительно ва-рьирует -от 20,6 до 83% [10][11][12][13][14].…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…The motility problems are believed to be secondary to a mass effect from the equatorial filtering bleb, a faden or posterior suture fixation effect, or fat adherence syndrome 20,10,14 . Almost all patients with motility disturbance had a large fibrous capsule surrounding the implant plate, adjacent muscles and sclera 21 .…”
Section: Motility Problemsmentioning
confidence: 99%